Einstein-Podolsky-Rosen correlations of ultracold atomic gases - Bar-Gill, Nir; Gross, Christian; Mazets, Igor; Oberthaler, Markus K.; Kurizki, Gershon (Physical review letters, 2011)
We demonstrate that collective continuous variables of two species of trapped ultracold bosonic gases can be Einstein-Podolsky-Rosen-correlated (entangled) via inherent interactions between the species. We propose two different schemes for creating these correlations—a dynamical scheme and a static scheme analogous to two-mode squeezing in quantum optics. We quantify the correlations by using known measures of entanglement and study the effect of finite temperature on these quantum correlations.